Pembentukan dan Pelatihan Kader Kesehatan Anak Berkebutuhan Khusus tentang Protokol Kesehatan Masa Pandemi COVID-19 - Risya Cilmiaty A. R.; Ida Nurwati; Selfi Handayani; Muthmainah Muthmainah; Dyah Ratna Budiani; Betty Saptiwi; Sarsono Sarsono; Martini Martini; Danus Hermawan; Jarot Subandono (Abdimas Universal, 2022)
The incidence of COVID-19 in Indonesia is significantly increasing. In Indonesia, there were 965.283 confirmed cases and 27.453 people died of covid as of January 22, 2021. Meanwhile, the 7.505 confirmed cases and 352 death were from Surakarta. In this pandemic situation, the community must protect itself from being infected by the virus. Prevention is done by implementating the 5M health protocol, which are wearing mask, social distancing, and hand washing. Those health protocols are also part of clean and healthy lifestyle (PHBS). Special needs children (ABK) are those who have different characteristics than any other common children. Special health consideration should be given for those special needs child, including PHBS because of the special needs they are having and probable difficulties into implementing PHBS. The consideration can be given by their teacher, caretaker, parents, or trained social health workers in the hope of special needs children become independent into implementing the PHBS. The aim of this program is implementating social service program and helping special needs children to become independent in implementating PHBS and health protocol. The program was held by lecturing, demonstration, simulation, and supervised practice. This program hopefully will prevent either health issues or prevent the spreading of infective disease, specifically in this pandemic situation.